Catalytic activation of unstrained C(aryl)-C(aryl) bonds in 2,2’-biphenols - Zhu, Jun (Nat Chem, 2018)
Transition-metal catalysis has emerged as an important means for C-C activation allowing mild and selective transformations. However, the current scope of C-C bonds that can be activated is primarily restricted to either highly strained systems or more polarized C-C bonds. In contrast, catalytic activation of nonpolar and unstrained C-C moieties remains an unmet challenge. Here we report a general approach for catalytic activation of the unstrained C(aryl)-C(aryl) bonds in 2,2’-biphenols. The key is utilizing the phenol moiety as a handle to install phosphinites as a recyclable directing group. Using hydrogen gas as the reductant, mono-phenols are obtained with a low catalyst loading and high functional group tolerance. This approach has also been applied to the synthesis of 2,3,4-trisubstituted phenols. Further mechanistic study suggests that the C-C activation step is mediated by a rhodium(I) mono-hydride species. Finally, a preliminary study on breaking the inert biphenolic moieties in lignin models is illustrated.